THE INFLUENCE OF WORK MOTIVATION, LEADERSHIP, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT MAYORA INDAH TBK - Fitri Febriani; Justine Tanuwijaya (SEAN Institute, 2022)
This study aims to test and analyze the influence of work motivation, leadership, and work environment on employee performance in PT Mayora Indah Tbk employees in the HR&GA (Human Resource & General Affairs) division and will then be mentioned with HR&GA information. The research conducted is quantitative research by distributing questionnaires. This study used hypot hesis testing method. Hypothesis testing using multiple regression analysis with SPSS software. The data in the study was collected from 117 employees of PT Mayora Indah Tbk in the HR&GA division using the census method. Based on the results of the study showing that there is no positive influence of work motivation on employee performance,there is no positive influence of leadership on employee performance and the work environment has a positive and significant effecton employee performance.